DEM NGULON–Based Symbolic Modeling as a Group Guidance Intervention for Entrepreneurial Behavior Development - Abdillah Arif; M. Solehuddin; Uman Suherman; Yusi Riksa Yustiana (Universitas PGRI Yogyakarta, 2026)
This study aims to develop and examine the effectiveness of the DEM NGULON-Based Symbolic Modeling technique in fostering entrepreneurial behavior among high school students. Although Symbolic Modeling has been shown to strengthen motivation and self-efficacy, limited research has examined how integrating local cultural values can enhance its impact in entrepreneurship education. Using a Collaborative Action Research approach, the intervention was implemented over four cycles, with guidance counselors and students as partners. The technique was structured into six reflective stages to support the internalization of values. Five aspects of entrepreneurial behavior were measured: innovativeness, risk-taking, hard work, managerial ability, and decision-making. The results indicate significant improvements in innovativeness, risk-taking, and managerial ability during Cycle I (p < 0.05), while other aspects showed no significant change. In Cycles II to IV, changes continued in a consolidation pattern. Students with lower initial scores recorded the greatest improvements. These findings highlight the contribution of positioning DEM NGULON as a culturally grounded reinforcement mechanism within modeling-based guidance. The study suggests that this approach can serve as an early catalyst for behavioral change and offers a relevant framework for entrepreneurship education that aligns psychological learning processes with local values. Keywords: action research, DEM NGULON, entrepreneurial behavior, high school students, symbolic modeling